Providing absolute quality of service guarantees in passive optical networks = Pružanje potpunih jamstava kvalitete usluge u pasivnim optičkim mrežama: doctoral thesis = doktorski rad - Beriša, Tomaž (T. Beriša ; Fakultet elektrotehnike i računarstva, 2010)
Title Providing absolute quality of service guarantees in passive optical networks Summary The thesis addresses issues related to absolute (parameterized) Quality of Service (QoS) guarantees for Passive Optical Networks (PON). It focuses on the problem of providing absolute bandwidth, delay and delay variation guarantees based on Service Level Agreements (SLA). Dynamic Bandwidth Allocation (DBA) algorithms are proposed to support all of the mentioned elements of QoS for PONs. Additionally, lower bounds for providing the mentioned guarantees are also formally defined and analyzed. From a networking standpoint, Optical Coding (OC) enabled PONs are investigated as an architecture upgrade to conventional PONs and its implications on DBAs and QoS guarantees are analyzed. DBA algorithms that provide absolute QoS guarantees in this setting are proposed and their boundaries are also formally defined and analyzed.